Composite transmission layer, perovskite solar cell and preparation method of perovskite solar cell

By setting the transition layer and buffer layer up and down the hole transport layer of the perovskite solar cell and adding coupling agent to the material to form a specific array structure, the perovskite solar cell is solved between conversion efficiency and stability. The light stability and conversion efficiency are significantly improved.

CN119156030APending Publication Date: 2024-12-17HANGZHOU MICROQUANTA SEMICON CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310711396.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The hole transport layer of existing perovskite solar cells is difficult to take into account both the conversion efficiency and the stability. High conversion efficiency is usually accompanied by poor photothermal stability, especially when the material is easily decomposed under long-term light, resulting in rapid attenuation of performance.

Method used

A composite transport layer structure is adopted, in which a transition layer and a buffer layer are arranged on the upper and lower sides of the hole transport layer, and a coupling agent is added to the preparation material of the transition layer and buffer layer to form a plurality of discretely arranged array molecular groups and spaced phases. adjacent openings to improve the conductivity and stability of the material.

Benefits of technology

It significantly improves the light stability and conversion efficiency of perovskite solar cells, extends the service life of the device, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156030A_ABST
    Figure CN119156030A_ABST
Patent Text Reader

Abstract

The invention relates to a composite transmission layer, a perovskite solar cell and a preparation method of the perovskite solar cell. The composite transmission layer comprises a transition layer, a hole transmission layer and a buffer layer which are sequentially stacked in the light incidence direction. The preparation material of the transition layer is Ni < x > A < y > Si < z > Sn < m > On or Cu < x > A < y > Si < z > Sn < m > On, 0, ygt; zgt is equal to 0; mgt = 0, mgt; ngt is equal to 0; 0 and A are aluminum or boron, a preparation material of the transition layer at least comprises any one element of A, Si and Sn, a preparation material of the hole transport layer is any one element of NiOx, CuxO and CuSCN, and a preparation material of the buffer layer is NiaEbNcOd or CuaEbNcOd, 0, bgt; cgt = 0; 0, dgt; e is any one of Al, B, Si, Zn, Co and Zr. The composite transmission layer is used in the perovskite solar cell, high defect density and high hole mobility of the hole transmission material are reserved, and the perovskite solar cell comprising the composite transmission layer has the advantages of being high in conversion efficiency and good in long-term photo-thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cell preparation, and in particular relates to a composite transmission layer and a perovskite solar cell and a preparation method thereof. Background Art

[0002] The common device structures of perovskite solar cells include positive-type NIP cell devices and inverted-type PIN cell devices, wherein the positive-type device refers to at least including, starting from the light incident surface, the following: transparent conductive layer, electron transport layer, perovskite active layer, hole transport layer and back electrode, and the inverted-type device refers to at least including, starting from the light incident surface, the following: transparent conductive layer, hole transport layer, perovskite active layer, electron transport layer and back electrode. Compared with positive-type devices, inverted-type devices do not require the use of TiO2 with high photocatalytic activity and expensive hole transport material Spiro-OMeTAD, can be prepared at low temperature, have simple processes and good stability. Despite this, most of the current high conversion efficiencies are positive-type devices, with the highest reaching 26%, but the conversion efficiency of inverted-type devices is mostly concentrated in the range of 22-24%. In inverted-type devices, further optimization of the hole transport layer and interface is crucial to improving the conversion efficiency of inverted-type cell devices.

[0003] The main reasons for the low conversion efficiency of inverted PIN cell devices are: the energy band mismatch between the first interface formed by the transparent conductive layer and the hole transport layer, and the large number of interface defects between the second interface formed by the hole transport layer and the perovskite active layer. The optional materials for the hole transport layer are generally divided into three categories: 1) inorganic oxides or inorganic salts; 2) organic polymers; 3) organic small molecules. Among them, the typical options for the first type of inorganic oxides or inorganic salts include NiO x , V2O5, CuO, CuSCN, etc.; Typical options for the second type of organic polymers include P3HT, PTAA, etc.; Typical options for the third type of organic small molecules include spiro-OMeTAD and PAC z The first type of material is easy to obtain and low in cost, but its good hole transport performance comes from the defects of the material itself. It often requires a higher defect density to obtain better hole transport performance. However, a higher defect density will make the photothermal stability of the second interface between the hole transport layer and the perovskite active layer worse, making it difficult to achieve both high conversion efficiency and good stability. x For example, in order to improve its hole mobility, it is necessary to increase the uncoordinated Ni 3+ concentration, but high concentration of Ni 3+ It also promotes NiO xThe source of the photocatalytic reaction at the perovskite interface. The second type of material generally requires a longer synthesis path, has better hole transport performance, and is easier to obtain an inversion device with high conversion efficiency. Its biggest shortcoming is that the polymer material itself has poor photostability and is prone to decomposition under long-term outdoor light conditions, resulting in rapid performance decay of the inversion device. The third type of material can further improve the conversion efficiency of the inversion device on the basis of the second type of material, but similar to the second type of material, due to the use of organic matter, the stability is poor under long-term light. In order to solve these problems, there are also reports on the use of a composite structure of an inorganic hole transport layer and an organic hole transport layer or a method of passivating an inorganic hole transport layer. However, the use of a composite structure of an inorganic hole transport layer and an organic hole transport layer is an indicator-free solution, because under long-term light, the organic layer will still decompose, causing the effect of this composite structure to disappear. The passivation of the inorganic hole transport layer is often a stopgap measure in exchange for improved stability at the expense of conversion efficiency.

[0004] In addition, the existing hole transport layer is generally made of inorganic oxides. The hole transport layer of inorganic oxides has the following problems: 1) The structure formed by inorganic oxides may be too dense, and hole conduction may encounter some problems; 2) Inorganic nanocrystals are prone to agglomeration during long-term use due to charge imbalance caused by surface defects. Once agglomerated, it will affect the stability of the material; 3) There are a large number of disordered dangling bonds on the surface of the inorganic interface, some of which will react with the perovskite material.

[0005] The existing hole transport layer cannot enable perovskite solar cells to have both high conversion efficiency and good stability. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a composite transport layer and a perovskite solar cell and a preparation method thereof, wherein the hole transport layer uses a composite structure, and a transition layer and a buffer layer are respectively arranged on the upper and lower surfaces of the hole transport layer, thereby retaining the high defect density and high hole mobility of the hole transport material, which not only greatly improves the light stability of the perovskite solar cell, but also improves the conversion efficiency of the perovskite solar cell. On the other hand, a coupling agent is doped in the preparation material of the composite transport layer to improve the conduction performance and stability of the hole transport layer made of an inorganic oxide material, so that the manufactured perovskite solar cell has the characteristics of high conversion efficiency and good stability.

[0007] The present invention is implemented by providing a first composite transmission layer, comprising a transition layer, a hole transmission layer and a buffer layer stacked in sequence according to the light incident direction, wherein the preparation material of the transition layer is Ni x A y Si z Sn m On or Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum (Al) or boron (B), the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d or Cu a E b N c O d , where a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr.

[0008] The present invention is implemented in this way, and also provides a second composite transmission layer, including a transition layer, a hole transmission layer and a buffer layer stacked in sequence according to the light incident direction, wherein the preparation material of the transition layer is Ni x A y Si z Sn m O n or Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d or Cu a E b N c O d, wherein a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr. A coupling agent is also added to the preparation material of the transition layer and / or the buffer layer to obtain a corresponding array transition layer and / or array buffer layer containing a coupling agent. The film made of the transition layer and / or buffer layer doped with a coupling agent contains a plurality of discretely arranged array molecular groups containing a coupling agent and openings separating two adjacent molecular groups, and each opening connects the upper and lower surfaces of the film. The coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.

[0009] The present invention is implemented in this way, and also provides a first perovskite solar cell, the internal structure of which includes a transparent conductive layer, a perovskite light absorbing layer, an electron transport layer and a back electrode stacked in sequence, and a first composite transport layer as described above is arranged between the transparent conductive layer and the perovskite light absorbing layer, the transition layer of the composite transport layer is in contact with the transparent conductive layer, and its buffer layer is in contact with the perovskite light absorbing layer.

[0010] The present invention is implemented in this way, and also provides a second perovskite solar cell, the internal structure of the perovskite solar cell includes a transparent conductive layer, a perovskite light absorbing layer, an electron transport layer and a back electrode stacked in sequence, and a second composite transport layer as described above is arranged between the transparent conductive layer and the perovskite light absorbing layer, the transition layer of the composite transport layer is in contact with the transparent conductive layer, and its buffer layer is in contact with the perovskite light absorbing layer.

[0011] The present invention is implemented in this way, and also provides a method for preparing the first perovskite solar cell as described above, comprising the following steps:

[0012] Step 1, cleaning and UV-ozone treating the transparent conductive layer;

[0013] Step 2: Prepare a transition layer on the transparent conductive layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the transition layer. The liquid phase method is to use any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method to prepare the transition layer.

[0014] Step 3: Prepare a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition device CVD device, a magnetron sputtering device, and a thermal evaporation device, or prepare a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process;

[0015] Step 4: prepare a buffer layer on the surface of the hole transport layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the buffer layer. The liquid phase method is to use any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method to prepare the buffer layer.

[0016] Step 5: Prepare a perovskite light absorbing layer, an electron transport layer and a back electrode in sequence on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

[0017] The present invention is implemented in this way, and also provides a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0018] Step I: cleaning and UV-ozone treating the transparent conductive layer;

[0019] Step II, mixing the coupling agent with the material solution for preparing the transition layer to obtain a first composite precursor solution, subjecting the first composite precursor solution to UV light treatment or high temperature treatment, and then coating the treated first composite precursor solution on the surface of the transparent conductive layer, and annealing and drying to obtain the transition layer;

[0020] Step III, preparing a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or preparing a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process;

[0021] Step IV, preparing a buffer layer on the surface of the hole transport layer using a gas phase method or a liquid phase method, the gas phase method is to use any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the buffer layer, and the liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method.

[0022] Step V: sequentially prepare a perovskite light absorbing layer, an electron transport layer and a back electrode on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

[0023] The present invention is implemented in this way, and also provides a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0024] Step 1, cleaning and UV-ozone treating the transparent conductive layer;

[0025] Step 2: prepare a transition layer on the transparent conductive layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the transition layer. The liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method.

[0026] Step 3: prepare a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process;

[0027] Step 4: Mix the coupling agent with the material solution for preparing the buffer layer to obtain a second composite precursor solution, subject the second composite precursor solution to UV light treatment or high temperature treatment, and then apply the treated second composite precursor solution on the surface of the hole transport layer, and anneal and dry to obtain the buffer layer;

[0028] Step 5: sequentially prepare a perovskite light absorbing layer, an electron transport layer and a back electrode on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

[0029] The present invention is implemented in this way, and also provides a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0030] Step A, cleaning and UV-ozone treating the transparent conductive layer;

[0031] Step B, mixing the coupling agent with the material solution for preparing the transition layer to obtain a first composite precursor solution, subjecting the first composite precursor solution to UV light treatment or high temperature treatment, and then coating the treated first composite precursor solution on the surface of the transparent conductive layer, and annealing and drying to obtain the transition layer;

[0032] Step C, preparing a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or preparing a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process;

[0033] Step D, mixing the coupling agent with the material solution for preparing the buffer layer to obtain a second composite precursor solution, subjecting the second composite precursor solution to UV light treatment or high temperature treatment, and then coating the treated second composite precursor solution on the surface of the hole transport layer, and annealing and drying to obtain the buffer layer;

[0034] Step E: sequentially preparing a perovskite light absorbing layer, an electron transport layer and a back electrode on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

[0035] The present invention utilizes the difference in wettability between the nanoparticles used to prepare the transition layer and / or buffer layer and the partially cross-linked coupling agent to form a continuous, regular, and discrete array of coupling agent-containing molecular clusters and openings separating two adjacent molecular clusters during film coating, thereby preparing an "array-shaped" transition layer and / or buffer layer containing the coupling agent.

[0036] Compared with the prior art, the first composite transport layer and perovskite solar cell and the preparation method thereof of the present invention include a transition layer, a hole transport layer and a buffer layer stacked in sequence according to the light incident direction. The preparation material of the transition layer is Ni x A y Si z Sn m O n or Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d or Cu a E b N c O d , wherein a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr. The hole transport layer of the present invention uses a composite structure, and a transition layer and a buffer layer are respectively arranged on the upper and lower surfaces of the hole transport layer, which retains the high defect density and high hole mobility of the hole transport material, so that the perovskite solar cell containing the composite transport layer has the characteristics of high conversion efficiency and good long-term light and heat stability.

[0037] On the other hand, compared with the prior art, the second composite transport layer and perovskite solar cell and the preparation method thereof of the present invention, the composite transport layer comprises a transition layer, a hole transport layer and a buffer layer stacked in sequence according to the light incident direction. The preparation material of the transition layer is Ni x A y Si z Sn m O n or Cu x A y Si z Snm O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d or Cu a E b N c O d , wherein a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr. A coupling agent is also added to the preparation material of the transition layer and / or the buffer layer to obtain a corresponding array transition layer and / or array buffer layer containing a coupling agent. The film made of the transition layer and / or the buffer layer doped with a coupling agent contains a plurality of discretely arranged array molecular groups containing a coupling agent and openings separating two adjacent molecular groups, and each opening connects the upper and lower surfaces of the film. The coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent. The hole transport layer of the present invention uses a composite array structure, and a coupling agent is added to the preparation material of the transition layer and / or the buffer layer to obtain an array transition layer and / or an array buffer layer, thereby improving the conduction performance and stability of the hole transport layer made of inorganic oxide materials, so that the prepared perovskite solar cell not only greatly improves the light stability of the perovskite solar cell, but also improves the conversion efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A schematic plan view of the internal structure of a preferred embodiment of the first perovskite solar cell of the present invention;

[0039] Figure 2 is a schematic plan view of a first internal structure of a second perovskite solar cell of the present invention;

[0040] Figure 3 is a schematic plan view of a second internal structure of a second perovskite solar cell of the present invention;

[0041] Figure 4 is a schematic plan view of a third internal structure of the second perovskite solar cell of the present invention;

[0042] Figure 5A schematic diagram comparing conversion efficiency curves of the perovskite solar cell prepared in Example 1 of the present invention and the perovskite solar cell prepared in Comparative Example 1;

[0043] Figure 6 A schematic diagram comparing the conversion efficiency of the perovskite solar cell prepared in Example 1 of the present invention and the perovskite solar cells prepared in Comparative Examples 2 and 3;

[0044] Figure 7 A comparison curve of aging test results of the perovskite solar cell prepared in Example 1 of the present invention and the perovskite solar cells of Comparative Examples 1 to 3;

[0045] Figure 8 for Figure 3 A three-dimensional schematic diagram of the composite transport layer of the second internal structure of the second perovskite solar cell;

[0046] Fig. 9 A schematic diagram comparing conversion efficiency curves of the perovskite solar cell prepared in Example 5 of the present invention and the perovskite solar cells of Comparative Examples 1, 3 and 4;

[0047] Fig.10 Schematic diagram comparing aging curves of the perovskite solar cell prepared in Example 5 of the present invention and the perovskite solar cells of Comparative Examples 1, 3 and 4. DETAILED DESCRIPTION

[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0049] Please refer to Figure 1 As shown, a preferred embodiment of the first composite transport layer of the present invention comprises a transition layer 1, a hole transport layer 2 and a buffer layer 3 stacked in sequence according to the light incident direction. The transition layer 1 is made of Ni x A y Si z Sn m O n or Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum (Al) or boron (B). The material for preparing the transition layer contains at least one element among A, Si, and Sn. The material for preparing the hole transport layer 2 is NiO x , Cu xO, CuSCN. The buffer layer 3 is made of Ni a E b N c O d or Cu a E b N c O d , where a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr.

[0050] Please also refer to Figures 2 to 4 As shown, a preferred embodiment of the second composite transport layer of the present invention comprises a transition layer 1, a hole transport layer 2 and a buffer layer 3 stacked in sequence according to the light incident direction. The preparation material of the transition layer 1 is Ni x A y Si z Sn m O n or Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, and the material for preparing the transition layer 1 contains at least one element among A, Si, and Sn. The material for preparing the hole transport layer 2 is NiO x , Cu x O, CuSCN. The buffer layer 3 is made of Ni a E b N c O d or Cu a E b N c O d , where a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr.

[0051] A coupling agent is also added to the preparation material of the transition layer 1 and / or the buffer layer 3, and the film made of the transition layer 1 and / or the buffer layer 3 doped with the coupling agent contains a plurality of discretely arranged array molecular groups 11 containing the coupling agent and openings 10 separating two adjacent molecular groups, and each opening 10 connects the upper and lower surfaces of the film respectively. The coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.

[0052] Specifically, the coupling agent is added in an amount of 0.5-5% of the volume of the nanoparticle suspension to be added to prepare the transition layer 1 and / or the buffer layer 3, and the concentration of the nanoparticle suspension is 0.1-10 wt.%.

[0053] Specifically, the length of the opening 10 (ie, the interval between two adjacent molecular clusters) is 10 nm to 200 nm.

[0054] Specifically, in the first composite transport layer and the second composite transport layer of the present invention, the thickness of the transition layer 1 is 0.2 nm to 30 nm, the thickness of the hole transport layer 2 is 1 nm to 100 nm, and the thickness of the buffer layer 3 is 0.2 nm to 50 nm.

[0055] Please refer to Figure 1 As shown, the present invention also discloses a first perovskite solar cell, the internal structure of which includes a transparent conductive layer 5, a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 stacked in sequence, and a first composite transport layer 4 as described above is arranged between the transparent conductive layer 5 and the perovskite light absorbing layer 6. The transition layer 1 of the composite transport layer 4 is in contact with the transparent conductive layer 5, and the buffer layer 3 thereof is in contact with the perovskite light absorbing layer 6. The hole transport layer 2 thereof is located between the transition layer 1 and the buffer layer 3.

[0056] Please refer to Figures 2 to 4 As shown, the present invention also discloses a second perovskite solar cell, the internal structure of which includes a transparent conductive layer 5, a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 stacked in sequence, and a second composite transport layer 4 as described above is arranged between the transparent conductive layer 5 and the perovskite light absorbing layer 6. The transition layer 1 of the composite transport layer 4 is in contact with the transparent conductive layer 5, and the buffer layer 3 thereof is in contact with the perovskite light absorbing layer 6. The hole transport layer 2 thereof is located between the transition layer 1 and the buffer layer 3.

[0057] In the first perovskite solar cell and the second perovskite solar cell of the present invention, the molecular formula of the material for preparing the perovskite light-absorbing layer 6 is ABX3, wherein A is at least one cation of cesium, rubidium, amine, amidine, and alkali groups, B is any one of divalent metal cations of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium, and X is any one of anions of iodine, bromine, chlorine, astatine, thiocyanate, and acetate.

[0058] The composite transmission layer of the second perovskite solar cell of the present invention has the following characteristics:

[0059] 1. When coating, the nanoparticles simply form openings, which solves the problem of the inorganic oxide layer structure being too dense, eliminates the influence of the thickness of the transition layer and the buffer layer on the electrical tunneling, reduces the non-radiative recombination between the interface of the perovskite light absorption layer and the hole transport layer, and does not affect the carrier transport.

[0060] 2. Inorganic nanocrystals tend to aggregate during long-term use due to charge imbalance caused by surface defects. Once aggregated, it will affect the stability of the material. The bonding and dispersing effects of the coupling agent avoid this phenomenon and improve the stability of the material and device.

[0061] 3. There are a large number of disordered dangling bonds on the surface of the inorganic interface. The use of coupling agents can also passivate the dangling bonds on the surface of the inorganic material, thereby inhibiting the photocatalytic reaction at the interface between the inorganic material and the perovskite, and further improving the stability.

[0062] Please refer to Figure 1 As shown, the present invention also discloses a method for preparing the first perovskite solar cell as described above, comprising the following steps:

[0063] Step 1: Clean and treat the transparent conductive layer 5 with ultraviolet ozone.

[0064] Step 2: Prepare the transition layer 1 on the transparent conductive layer 5 using a gas phase method or a liquid phase method. The gas phase method is to prepare the transition layer using any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, and the liquid phase method is to prepare the transition layer 1 using any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method.

[0065] Step 3: Prepare a hole transport layer 2 on the surface of the transition layer 1 using any one of an atomic layer deposition device ALD device, a chemical vapor deposition device CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare the hole transport layer 2 by any one of a solution blade coating, a slit coating, and a spray coating process.

[0066] Step 4: Prepare a buffer layer 3 on the surface of the hole transport layer 2 using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the buffer layer; the liquid phase method can use any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method to prepare the buffer layer 3.

[0067] Step 5: On the surface of the buffer layer 3, a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 are sequentially prepared until the preparation of the perovskite solar cell is completed.

[0068] Please refer to Figure 2As shown, the present invention also discloses a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0069] Step I: cleaning and treating the transparent conductive layer 5 with ultraviolet ozone.

[0070] Step II: Mix the coupling agent with the material solution for preparing the transition layer 1 to obtain a first composite precursor solution, subject the first composite precursor solution to UV light treatment or high temperature treatment, and then coat the treated first composite precursor solution on the surface of the transparent conductive layer 5, and obtain the array transition layer 1 after annealing and drying.

[0071] Step III: prepare a hole transport layer 2 on the surface of the transition layer 1 using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare the hole transport layer 2 by any one of a solution blade coating, a slit coating, and a spray coating process.

[0072] Step IV, prepare the buffer layer 3 on the surface of the hole transport layer 2 using a gas phase method or a liquid phase method. The gas phase method is to use any one of atomic layer deposition ALD equipment, chemical vapor deposition CVD equipment, magnetron sputtering equipment, electron beam evaporation equipment, and thermal evaporation equipment to prepare the buffer layer 3. The liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method.

[0073] Step V: sequentially prepare a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 on the surface of the buffer layer 3 until the preparation of the perovskite solar cell is completed.

[0074] Please refer to Figure 3 As shown, the present invention also discloses a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0075] Step 1: Clean and treat the transparent conductive layer 5 with ultraviolet ozone.

[0076] Step 2: Prepare a transition layer 1 on the transparent conductive layer 5 using a gas phase method or a liquid phase method. The gas phase method is to use any one of atomic layer deposition ALD equipment, chemical vapor deposition CVD equipment, magnetron sputtering equipment, electron beam evaporation equipment, and thermal evaporation equipment to prepare the transition layer 1. The liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method.

[0077] Step 3: Prepare a hole transport layer 2 on the surface of the transition layer 1 using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare the hole transport layer 2 by any one of a solution blade coating, a slit coating, and a spray coating process.

[0078] Step 4: Mix the coupling agent with the material solution for preparing the buffer layer 3 to obtain a second composite precursor solution, subject the second composite precursor solution to UV light treatment or high temperature treatment, and then coat the treated second composite precursor solution on the surface of the hole transport layer 2, and obtain the array buffer layer 3 after annealing and drying.

[0079] Step 5: sequentially prepare a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 on the surface of the buffer layer 3 until the preparation of the perovskite solar cell is completed.

[0080] Please refer to Figure 4 As shown, the present invention also discloses a method for preparing the second perovskite solar cell as described above, comprising the following steps:

[0081] Step A: cleaning and treating the transparent conductive layer 5 with ultraviolet ozone.

[0082] Step B: Mix the coupling agent with the material solution for preparing the transition layer 1 to obtain a first composite precursor solution, subject the first composite precursor solution to UV light treatment or high temperature treatment, and then coat the treated first composite precursor solution on the surface of the transparent conductive layer 5, and obtain the array transition layer 1 after annealing and drying.

[0083] Step C: prepare the hole transport layer 2 on the surface of the transition layer 1 using any one of atomic layer deposition ALD equipment, chemical vapor deposition CVD equipment, magnetron sputtering equipment, electron beam evaporation equipment, and thermal evaporation equipment, or prepare the hole transport layer 2 by any one of solution blade coating, slit coating, and spraying.

[0084] Step D: Mix the coupling agent with the material solution for preparing the buffer layer 3 to obtain a second composite precursor solution, treat the second composite precursor solution with UV light or high temperature, and then coat the treated second composite precursor solution on the surface of the hole transport layer 2, and obtain the array buffer layer 3 after annealing and drying.

[0085] Step E: sequentially prepare a perovskite light absorbing layer 6, an electron transport layer 7 and a back electrode 8 on the surface of the buffer layer 3 until the preparation of the perovskite solar cell is completed.

[0086] Specifically, the conditions of the UV light treatment are: the light wavelength range is 265nm to 365nm, and the light treatment time is 5min to 60min. The conditions of the high temperature treatment are: the heating temperature range is 50 to 100°C, and the heating treatment time is 5min to 60min.

[0087] The perovskite solar cell structure and the preparation method thereof of the present invention are further illustrated by specific examples below.

[0088] Example 1

[0089] Please refer to Figure 1 As shown, an embodiment of the method for preparing a first perovskite solar cell of the present invention comprises the following steps:

[0090] Step 11: The glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then dried with N2 and treated with UV O-zone for 10 minutes.

[0091] Step 12: Using a magnetron sputtering device, a transition layer 1 with a thickness of 0.2 nm to 30 nm is prepared on the surface of the transparent conductive layer 5 of FTO. The structural formula of the material of the transition layer 1 is Ni 0.15 Al 0.05 Sn 0.8 O 1.825 .

[0092] Step 13: Spin-coat a 0.15M nickel acetylacetonate ethanol solution on the surface of the transition layer 1 at 4000R for 30s, and then burn at 400°C for 30min to prepare a nickel oxide hole transport layer 2 with a thickness of 1nm to 100nm.

[0093] Step 14: Prepare the buffer layer 3 by solution combustion method. The structural formula of the buffer layer 3 material is NiN 0.3 O 0.7 , 29 mg of NiNO3·6H2O and 3 mg of urea solution were dissolved in 1 ml of deionized water, stirred, and a 0.2 nm to 50 nm thick buffer layer 3 film was prepared on the surface of the nickel oxide hole transport layer 2 by spray coating, and heated at 400°C for 30 min in N2 atmosphere and at 200°C for 10 min in air;

[0094] Step 15: Prepare the perovskite light absorbing layer 6 on the surface of the buffer layer 3 using a one-step solution method.

[0095] Step 16: sequentially coating an electron transport layer 7 (PCBM) and a barrier layer (BCP) on the surface of the perovskite light absorbing layer 6.

[0096] Step 17: Prepare a back electrode 8 (Ag) on ​​the surface of the electron transport layer 7 and the barrier layer until the preparation of the perovskite solar cell is completed.

[0097] Example 2

[0098] Please refer to Figure 1 As shown, an embodiment of the second method for preparing a perovskite solar cell of the present invention comprises the following steps:

[0099] Step 21, the glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then dried with N2 and treated with UV O-zone for 10 minutes.

[0100] Step 22: Prepare a transition layer 1 on the surface of the transparent conductive layer 5 of FTO by using a mixed solution method. The structural formula of the material of the transition layer 1 is Cu 0.05 Al 0.2 Sn 0.75 O 1.85 , 1.4 mg of CuCl2, 5.4 mg of AlCl3, and 28.5 mg of SnCl2 were dissolved in 1 ml of deionized water, stirred and set aside, and a 0.2 nm to 30 nm thick transition layer 1 film was prepared on the surface of the transparent conductive layer 5 of FTO by a doctor blade method, and heated at 500°C in air for 1 h to obtain the required transition layer 1.

[0101] Step 23: Use magnetron sputtering equipment to prepare a Cu layer with a thickness of 1 nm to 100 nm on the surface of the transition layer 1. x O hole transport layer 2.

[0102] Step 24: x The buffer layer 3 is prepared on the surface of the hole transport layer 2 by magnetron sputtering. The structural formula of the buffer layer 3 material is Cu 0.4 Al 0.6 O 1.1 .

[0103] Step 25: Prepare the perovskite light absorbing layer 6 on the surface of the buffer layer 3 using a one-step solution method.

[0104] Step 26: sequentially coating the electron transport layer 7 (C60) and the barrier layer zirconium acetylacetonate on the surface of the perovskite light absorbing layer 6.

[0105] Step 27: Prepare a back electrode 8 (Ag) on ​​the surface of the electron transport layer 7 and the barrier layer until the preparation of the perovskite solar cell is completed.

[0106] Example 3

[0107] Please refer to Figure 1 As shown, an embodiment of the third method for preparing a perovskite solar cell of the present invention comprises the following steps:

[0108] Step 31, the glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then dried with N2 and treated with UV O-zone for 10 minutes.

[0109] Step 32: prepare a 0.1M NiCl3, 0.1M AlCl3 hydrochloric acid solution, Fe as a catalyst, and treat for 10min to 30min. The treated FTO transparent conductive layer is heated at 500°C in air for 30min to prepare a transition layer 1 generated in situ by FTO, the structure of which is Ni 0.1 Al 0.11 Sn 0.8 O 1.9 .

[0110] Step 33: Spin-coat a 0.15M nickel acetylacetonate ethanol solution on the surface of the transition layer 1 at 4000R for 30s, and then burn at 400°C for 30min to prepare a nickel oxide hole transport layer 2.

[0111] Step 34: Prepare a buffer layer 3 on the surface of the hole transport layer 2 by CVD equipment under NH3 and O2 atmospheres respectively. The structural formula of the buffer layer 3 material is Ni 0.9 Al 0.1 N 0.1 O 0.9 .

[0112] Step 35: Prepare the perovskite light absorbing layer 6 on the surface of the buffer layer 3 using a one-step solution method.

[0113] Step 36: sequentially coat the electron transport layer 7 (C60 and SnO2) on the surface of the perovskite light absorption layer 6.

[0114] Step 37: Prepare a back electrode 8 (Cu) on the surface of the electron transport layer 7 until the preparation of the perovskite solar cell is completed.

[0115] Example 4

[0116] Please refer to Figure 1 As shown, an embodiment of the fourth method for preparing a perovskite solar cell of the present invention comprises the following steps:

[0117] Step 41, the glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then dried with N2 and treated with UV O-zone for 10 minutes.

[0118] Step 42: Prepare a transition layer 1 on the surface of the transparent conductive layer 5 of FTO using a CVD device. The structural formula of the material of the transition layer 1 is Cu 0.05 Al 0.2 Sn 0.75 O 1.85 .

[0119] Step 43: Prepare the CuSCN hole transport layer 2 on the surface of the transition layer 1 by using a solution method.

[0120] Step 44: deposit a nanocrystalline mixture of Cu2O and Al2O3 on the surface of the CuSCN hole transport layer 2 by scraping to prepare Cu 0.5 Al 0.5 O buffer layer 3.

[0121] Step 45 : preparing the perovskite light absorbing layer 6 on the surface of the buffer layer 3 by using a one-step solution method.

[0122] Step 46: sequentially coat the electron transport layer 7 (SnO2) on the surface of the perovskite light absorption layer 6.

[0123] Step 47: Prepare a back electrode 8 (Ag) on ​​the surface of the electron transport layer 7 until the preparation of the perovskite solar cell is completed.

[0124] The composite transmission layer of the first perovskite solar cell of the present invention has the following characteristics:

[0125] 1. Commonly used transparent conductive layers, such as FTO, are n-type doped. After the present invention introduces p-type doping such as Al, B, Si into the transition layer, a doping concentration gradient and energy level transition are formed between the transparent conductive layer and the hole transport layer. In addition, the buffer layer replaces organic matter with nitrogen-containing inorganic matter, which has good light and heat stability, passivates the surface defects of the hole transport layer, and improves the stability of the second interface between the hole transport layer and the perovskite light absorption layer.

[0126] 2. The perovskite solar cell of the present invention has greatly improved the light stability of the perovskite solar cell due to the use of a composite transmission layer. x As the hole transport layer, Ni is mainly composed of Ni 2+ 、Ni 3+ And a small amount of Ni 4+ In the form of 3+ Can improve carrier transport, but Ni 3+ The presence of high-priced Ni also causes Ni photocatalysis, affecting the light stability of perovskite solar cells. The transition layer proposed by the present invention allows the hole transport material to transition to the perovskite material, while controlling the Ni in the transition layer. 3+ As well as the proportion of high-priced Ni, the light stability of perovskite solar cells is greatly improved.

[0127] Please refer to Figure 5 As shown in FIG. 1 , the conversion efficiency curve of the perovskite solar cell (i.e., a 3-layer composite structure) prepared in Example 1 of the present invention is shown, and the conversion efficiency curve of the conventional perovskite solar cell (i.e., a single-layer hole transport layer) comprising a single-layer hole transport layer is shown in FIG. Figure 5It can be seen that the open circuit voltage of the perovskite solar cell containing the composite transport layer of the present invention is significantly improved, the open circuit voltage of the single-layer hole transport layer is 1.014V, and the voltage of the three-layer composite structure reaches 1.136V.

[0128] Please refer to Figure 6 , Comparative Example 2 is a conversion efficiency curve of a double-layer perovskite solar cell including a transition layer and a hole transport layer (i.e., transition layer + hole transport layer), and Comparative Example 3 is a conversion efficiency curve of a double-layer perovskite solar cell including a hole transport layer and a buffer layer (i.e., hole transport layer + buffer layer). Figure 6 It can be seen that Example 1 significantly improves Jsc and Voc compared to Comparative Example 2), and significantly improves FF compared to Comparative Example 3, and further improves Voc, with an efficiency of 19.64%.

[0129] Please refer to Figure 7 As shown, the aging test curve of the perovskite solar cell prepared in Example 1 of the present invention (i.e., a three-layer composite structure), the aging test curve of the perovskite solar cell of Comparative Example 1 (i.e., a single-layer hole transport layer), the aging test curve of the perovskite solar cell of Comparative Example 2 (i.e., a double-layer structure of a transition layer + a hole transport layer), and the aging test curve of the perovskite solar cell of Comparative Example 3 (i.e., a double-layer structure of a hole transport layer + a buffer layer). Figure 7 It can be seen that the light aging stability of the perovskite solar cells in Comparative Examples 2 and 3 is improved compared with that in Comparative Example 1. The light aging attenuation of the perovskite solar cell in Example 1 of the present invention is less than 5% after 3500 hours, which is significantly better than the test results of the perovskite solar cells in Comparative Examples 1 to 3.

[0130] Example 5

[0131] Please refer to Figure 2 As shown, an embodiment of the method for preparing the second perovskite solar cell of the present invention comprises the following steps:

[0132] Step 51, the glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then blown dry with N2 and treated with UV O-zone for 10 minutes.

[0133] Step 52, 3-aminopropyltriethoxysilane and Al2O3 and SnO2 nanoparticles (10wt%, 100nm) suspension are mixed in IPA at a volume ratio of 1%, stirred and mixed, and irradiated under a 365nm UV lamp for 10 minutes for use; the mixed suspension is coated on the FTO transparent conductive layer 5 by a doctor blade method, and the wet film is heated and annealed to form an array transition layer 1 containing an opening 10.

[0134] Step 53: Spin-coat a 0.15M nickel acetylacetonate ethanol solution on the surface of the transition layer 1 at 4000R for 30s, and then burn at 400°C for 30min to prepare a nickel oxide hole transport layer 2 with a thickness of 1nm to 100nm.

[0135] Step 54: Prepare the buffer layer 3 by solution combustion method. The structural formula of the buffer layer 3 material is NiN 0.3 O 0.7 , 29 mg of NiNO3·6H2O and 3 mg of urea solution were dissolved in 1 ml of deionized water, stirred, and a 0.2 nm to 50 nm thick buffer layer 3 film was prepared on the surface of the nickel oxide hole transport layer 2 by spraying, and heated at 400°C for 30 min in N2 atmosphere and at 200°C for 10 min in air.

[0136] Step 55 : preparing the perovskite light absorbing layer 6 on the surface of the buffer layer 3 by using a one-step solution method.

[0137] Step 56: sequentially coat the electron transport layer 7 (PCBM) and the barrier layer (BCP) on the surface of the perovskite light absorbing layer 6.

[0138] Step 57: Prepare a back electrode 8 (Ag) on ​​the surface of the electron transport layer 7 and the barrier layer until the preparation of the perovskite solar cell is completed.

[0139] Example 6

[0140] Please refer to Figure 3 and Figure 8 As shown, another embodiment of the method for preparing the second perovskite solar cell of the present invention comprises the following steps:

[0141] Step 61, the glass on which the FTO transparent conductive layer 5 has been prepared is cleaned with detergent, deionized water, acetone, and isopropanol ultrasonically for 30 minutes each, then dried with N2 and treated with UV O-zone for 10 minutes.

[0142] Step 62: Prepare a transition layer 1 with a thickness of 0.2 nm to 30 nm on the surface of the transparent conductive layer 5 of FTO by using a mixed solution method. The structural formula of the material of the transition layer 1 is Cu 0.05 Al 0.2 Sn 0.75 O 1.85 , 1.4 mg of CuCl2, 5.4 mg of AlCl3, and 28.5 mg of SnCl2 were dissolved in 1 ml of deionized water, stirred and set aside, and a transition layer 1 film was prepared on the surface of the transparent conductive layer 5 of FTO by a doctor blade method, and heated at 500°C in air for 1 h to obtain the required transition layer 1.

[0143] Step 63: Use magnetron sputtering equipment to prepare a Cu layer with a thickness of 1 nm to 100 nm on the surface of the transition layer 1. x O hole transport layer 2.

[0144] Step 64: Vinyltriethoxysilane and Cu x O and SiO2 nanoparticles (10wt%, 80nm) suspension were mixed in deionized water at a volume ratio of 1%, and the mixed solution was heated and stirred at 80-100°C for 30min for use; the mixed suspension was coated on Cu by a doctor blade method. x On the hole transport layer 2, an array buffer layer 3 containing openings 10 is obtained after annealing.

[0145] Step 65 : Prepare the perovskite light absorbing layer 6 on the surface of the buffer layer 3 using a one-step solution method.

[0146] Step 66: sequentially coat the electron transport layer 7 (C60) and the barrier layer (zirconium acetylacetonate) on the surface of the perovskite light absorbing layer 6.

[0147] Step 67: Prepare a back electrode 8 (Ag) on ​​the surface of the electron transport layer 7 and the barrier layer until the preparation of the perovskite solar cell is completed.

[0148] The composite transport layer of the second perovskite solar cell of the present invention also has the following characteristics:

[0149] 1. Commonly used transparent conductive layers, such as FTO, are n-type doped. After the present invention introduces p-type doping such as Al, B, Si into the transition layer, a doping concentration gradient and energy level transition are formed between the transparent conductive layer and the hole transport layer. In addition, the buffer layer replaces organic matter with nitrogen-containing inorganic matter, which has good light and heat stability, passivates the surface defects of the hole transport layer, and improves the stability of the second interface between the hole transport layer and the perovskite light absorption layer.

[0150] 2. The perovskite solar cell of the present invention has greatly improved the light stability of the perovskite solar cell due to the use of a composite transmission layer. x As the hole transport layer, Ni is mainly composed of Ni 2+ 、Ni 3+ And a small amount of Ni 4+ In the form of 3+ Can improve carrier transport, but Ni 3+ The presence of high-priced Ni also causes Ni photocatalysis, affecting the light stability of perovskite solar cells. The transition layer proposed by the present invention allows the hole transport material to transition to the perovskite material, while controlling the Ni in the transition layer. 3+ As well as the proportion of high-priced Ni, the light stability of perovskite solar cells is greatly improved.

[0151] 3. When coating, the nanoparticles simply form openings, which solves the problem of the inorganic oxide layer structure being too dense, eliminates the influence of the thickness of the transition layer and the buffer layer on the electrical tunneling, reduces the non-radiative recombination between the interface of the perovskite light absorption layer and the hole transport layer, and does not affect the carrier transport.

[0152] 4. Inorganic nanocrystals tend to aggregate during long-term use due to charge imbalance caused by surface defects. Once aggregated, it will affect the stability of the material. The bonding and dispersing effects of the coupling agent avoid this phenomenon and improve the stability of the material and device.

[0153] 5. There are a large number of disordered dangling bonds on the surface of the inorganic interface. The use of coupling agents can also passivate the dangling bonds on the surface of the inorganic material, thereby inhibiting the photocatalytic reaction at the interface between the inorganic material and the perovskite, and further improving the stability.

[0154] Please refer to Fig. 9 As shown, the conversion efficiency curve of the perovskite solar cell (i.e., three-layer structure / including array transition layer) prepared in Example 5 of the present invention, Comparative Example 1 is the conversion efficiency curve of the existing perovskite solar cell containing a single hole transport layer (i.e., single hole transport layer), Comparative Example 4 is the conversion efficiency curve of a perovskite solar cell containing an array transition layer and a hole transport layer (i.e., array transition layer / hole transport layer), and Comparative Example 3 is the conversion efficiency curve of a perovskite solar cell containing a hole transport layer and a buffer layer (i.e., hole transport layer / buffer layer). The difference between Comparative Example 4 and Example 6 is that Comparative Example 4 does not contain a buffer layer. The difference between Comparative Example 3 and Example 6 is that Comparative Example 3 does not contain a transition layer and the buffer layer is not in an array shape. By Fig. 9 It can be seen that the open circuit voltage and fill factor of the three-layer hole transport composite structure including Example 5 of the present invention are significantly improved compared with Comparative Examples 1, 4 and 3. The open circuit voltage of the perovskite solar cell of Example 5 of the present invention reaches 1.147V and the FF reaches 79.23%. Fig. 9 and Figure 5 By comparison, it can be seen that the efficiency of the perovskite solar cell device prepared by the three-layer composite structure including the array structure is also better than that of the three-layer composite structure without the array. The open circuit voltage is increased from 1.136V to 1.147V, the fill factor is significantly improved from 76.62% to 79.23%, and the conversion efficiency is increased from 19.64% to 20.34%, and the conversion efficiency is increased by about 3.6%.

[0155] Please refer to Fig.10As shown, the light aging test curve of the perovskite solar cell (i.e., three-layer structure / containing an array-shaped transition layer) prepared in Example 5 of the present invention, Comparative Example 1 is the light aging test curve of the existing perovskite solar cell containing a single-layer hole transport layer (i.e., a single-layer hole transport layer), Comparative Example 4 is the light aging test curve of a perovskite solar cell containing an array transition layer and a hole transport layer (i.e., an array transition layer / hole transport layer), and Comparative Example 3 is the light aging test curve of a perovskite solar cell containing a hole transport layer and a buffer layer (i.e., a hole transport layer / buffer layer). The light stability of Comparative Examples 4 and 5 is significantly improved compared to that of Comparative Example 1, but the aging test results of the perovskite solar cell prepared in Example 5 of the present invention are significantly better than those of Comparative Examples 1, 4, and 3, and the light stability is greatly improved, with no attenuation after 2000 hours of light aging, and attenuation of less than 3% after 3500 hours. At the same time, compared Figure 7 and Fig.10 The light stability of the perovskite solar cell device prepared with a three-layer composite structure including an array structure is also better than that of the three-layer composite structure without an array, and the attenuation after 3500 hours is reduced from about 5% to less than 3%.

[0156] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite transmission layer, characterized in that: It includes a transition layer, a hole transport layer and a buffer layer stacked in sequence according to the light incident direction, and the preparation material of the transition layer is Ni x A y Si z Sn m O n Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d Cu a E b N c O d , where a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr.

2. A composite transmission layer, characterized in that: It includes a transition layer, a hole transport layer and a buffer layer stacked in sequence according to the light incident direction, and the preparation material of the transition layer is Ni x A y Si z Sn m O n Cu x A y Si z Sn m O n , wherein x>0, y>=0, z>=0, m>=0, n>0, A is aluminum or boron, the material for preparing the transition layer contains at least one element of A, Si, Sn, and the material for preparing the hole transport layer is NiO x , Cu x O, CuSCN, the buffer layer is made of Ni a E b N c O d Cu a E b N c O d , wherein a>0, b>=0, c>0, d>=0, and E is any one of Al, B, Si, Zn, Co, and Zr; a coupling agent is also added to the preparation material of the transition layer and / or the buffer layer to obtain a corresponding array transition layer and / or array buffer layer containing a coupling agent, and the film made of the transition layer and / or buffer layer doped with a coupling agent contains a plurality of discretely arranged array molecular clusters containing a coupling agent and openings separating two adjacent molecular clusters, each opening respectively connects the upper and lower surfaces of the film, and the coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.

3. The composite transmission layer according to claim 2, characterized in that The coupling agent is added in an amount of 0.5-5% of the volume of the nanoparticle suspension to be added to prepare the transition layer and / or buffer layer, and the concentration of the nanoparticle suspension is 0.1-10 wt.%.

4. The composite transmission layer according to claim 2, characterized in that The length of the opening is 10 nm to 200 nm.

5. The composite transmission layer according to claim 1 or 2, characterized in that: The thickness of the transition layer is 0.2nm-30nm, the thickness of the hole transport layer is 1nm-100nm, and the thickness of the buffer layer is 0.2nm-50nm.

6. A perovskite solar cell, wherein the internal structure of the perovskite solar cell comprises a transparent conductive layer, a perovskite light absorbing layer, an electron transport layer and a back electrode stacked in sequence, characterized in that: The composite transmission layer according to claim 1 is arranged between the transparent conductive layer and the perovskite light absorbing layer, the transition layer of the composite transmission layer is in contact with the transparent conductive layer, and the buffer layer thereof is in contact with the perovskite light absorbing layer.

7. A perovskite solar cell, wherein the internal structure of the perovskite solar cell comprises a transparent conductive layer, a perovskite light absorbing layer, an electron transport layer and a back electrode stacked in sequence, characterized in that: The composite transmission layer as claimed in claim 2 is arranged between the transparent conductive layer and the perovskite light absorbing layer, the transition layer of the composite transmission layer is in contact with the transparent conductive layer, and the buffer layer thereof is in contact with the perovskite light absorbing layer.

8. A method for preparing a perovskite solar cell according to claim 6, characterized in that: The steps include: Step 1, cleaning and UV-ozone treating the transparent conductive layer; Step 2: Prepare a transition layer on the transparent conductive layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the transition layer. The liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method. Step 3: prepare a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process; Step 4: prepare a buffer layer on the surface of the hole transport layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition device ALD, a chemical vapor deposition device CVD, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the buffer layer. The liquid phase method is to use any one of a mixed solution method, a hydrothermal method, a chemical bath, and an in-situ doping method to prepare the buffer layer. Step 5: Prepare a perovskite light absorbing layer, an electron transport layer and a back electrode in sequence on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

9. A method for preparing a perovskite solar cell according to claim 7, characterized in that: The steps include: Step I: cleaning and UV-ozone treating the transparent conductive layer; Step II, mixing the coupling agent with the material solution for preparing the transition layer to obtain a first composite precursor solution, subjecting the first composite precursor solution to UV light treatment or high temperature treatment, and then coating the treated first composite precursor solution on the surface of the transparent conductive layer, and annealing and drying to obtain an array transition layer; Step III, preparing a hole transport layer on the surface of the array transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or preparing a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process; Step IV, preparing a buffer layer on the surface of the hole transport layer using a gas phase method or a liquid phase method, the gas phase method is to use any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the buffer layer, and the liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method. Step V: sequentially prepare a perovskite light absorbing layer, an electron transport layer and a back electrode on the surface of the buffer layer until the preparation of the perovskite solar cell is completed.

10. A method for preparing a perovskite solar cell according to claim 7, characterized in that: The steps include: Step 1, cleaning and UV-ozone treating the transparent conductive layer; Step 2: prepare a transition layer on the transparent conductive layer using a gas phase method or a liquid phase method. The gas phase method is to use any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device to prepare the transition layer. The liquid phase method is any one of a mixed solution method, a hydrothermal method, a chemical bath method, and an in-situ doping method. Step 3: prepare a hole transport layer on the surface of the transition layer using any one of an atomic layer deposition ALD device, a chemical vapor deposition CVD device, a magnetron sputtering device, an electron beam evaporation device, and a thermal evaporation device, or prepare a hole transport layer by any one of a solution blade coating, a slit coating, and a spray coating process; Step 4: Mix the coupling agent with the material solution for preparing the buffer layer to obtain a second composite precursor solution, subject the second composite precursor solution to UV light treatment or high temperature treatment, and then apply the treated second composite precursor solution on the surface of the hole transport layer, and anneal and dry to obtain the array buffer layer; Step 5: sequentially prepare a perovskite light absorbing layer, an electron transport layer and a back electrode on the surface of the array buffer layer until the preparation of the perovskite solar cell is completed.

Citation Information

Cited By

  • Solar cell, preparation method thereof and photovoltaic module

    CN120379446A

  • Solar cell and preparation method thereof, photovoltaic module

    CN120379446B